Introduction: Ethnic Nationalism and Politicized Religion in the Pakistan-Afghanistan Borderland - Brasher, Ryan (The review of faith & international affairs, 2023)
There is a presumed tension between nationalism and religious ideology in the context of ethno-linguistic communities in the contemporary politics of Central and South Asia. This essay introduces a series of articles that explore these issues along the Pakistan and Afghanistan borderland. Together we explore how religion, nationalism, and ethnic identity interact with one another to shape political phenomena in Afghanistan, Pakistan, and its turbulent border region. We examine the extent to which ethno-linguistic and religious identities interact with, reinforce each other, and at times may come into conflict with one another.